ANALISIS ANTREAN DENGAN SISTEM JUMLAH KEDATANGAN BERDISTRIBUSI BETA, WEIBULL, NORMAL, DAN ERLANG (STUDI KASUS GERBANG TOL MUKTIHARJO) - Sugito Sugito; Erna Musri Arlita; Diah Safitri; Abdul Hoyyi; Rita Rachmawati (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2018)
Semarang is the capital city of Central Java Province so that development in Semarang City progressed very rapidly, this requires transportation facilities and infrastructure that good, smoothly and efficiently. One of the important transport infrastructure for Semarang City is a toll road. Muktiharjo toll gate is one of the exiting toll gate in Semarang City. Muktiharjo toll gate provides two types of service namely booths toll booths, a regular and automated toll booths. The existances two types of toll booths that provided the analysis needs to be done, then the line to find out how the system line that is in Muktiharjo toll gate. The research result obtained the model line at the Muktiharjo toll gate (BETA / G / 3) :( GD / ¥ / ¥) for regular toll road of Surabaya-Semarang direction, (WEIB / G / 1) :( GD / ¥ / ¥) for the Surabaya-Semarang automatic toll booth, (NORM / G / 2) :( GD / ¥ / ¥) for the regular toll road of Semarang-Surabaya and (ERLA / G / 2) :( GD / ¥ / ¥) Semarang-Surabaya automatic toll road. Based on simulation using Arena software, the addition of substations can reduce the waiting time of vehicles in line, while substation reduction can extend the waiting time of vehicles in line.Keyword : Queue theory, Queue simulation, Regular toll gate, Automatic toll gate, Arrival, Service.